2017
DOI: 10.1016/j.wear.2016.12.055
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of frictional response of shed snakeskin and human skin

Abstract: Skin in biological systems, including humans, perform several synchronized tasks (mechanical, protective, tactile, sensory, etc.). Tribological function is among skin tasks and may determine the survivability of many species. Cross comparison of tribological functional traits of skin of different species, albeit interesting, is rarely encountered, if at all exists, in tribology literature. One interesting example is that of snake and human skins. This skin pair was the subject of many studies for transdermal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 91 publications
0
17
0
Order By: Relevance
“…Previous experimental studies have shown that the interaction of the human skin with different materials and surfaces can show coefficient of friction over a wide range, between 0.059 and 3.7 [ 44 , 107 , 108 ]. Although our analysis does not represent the interaction between the human skin and particular materials, values of μ = 0.25 have been reported for the interaction between calf skin and nitrocellulose [ 29 ], μ = 0.22 for the contact between forearm skin and stainless steel [ 109 ], μ = 0.22 between forearm and polypropylene and between different body zones and Teflon [ 27 ], and μ = 0.19 between forearm skin and steel [ 44 ] among other similar values to the local coefficient of friction considered here. Previous work considering rigid indenters and soft substrate showed that the reaction forces on the indenter are not just due to the local friction but that an asymmetric deformation field on the length scale of the indenter can contribute a significant deformation component [ 33 , 34 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experimental studies have shown that the interaction of the human skin with different materials and surfaces can show coefficient of friction over a wide range, between 0.059 and 3.7 [ 44 , 107 , 108 ]. Although our analysis does not represent the interaction between the human skin and particular materials, values of μ = 0.25 have been reported for the interaction between calf skin and nitrocellulose [ 29 ], μ = 0.22 for the contact between forearm skin and stainless steel [ 109 ], μ = 0.22 between forearm and polypropylene and between different body zones and Teflon [ 27 ], and μ = 0.19 between forearm skin and steel [ 44 ] among other similar values to the local coefficient of friction considered here. Previous work considering rigid indenters and soft substrate showed that the reaction forces on the indenter are not just due to the local friction but that an asymmetric deformation field on the length scale of the indenter can contribute a significant deformation component [ 33 , 34 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…It operates physiologically in the large deformation regime and shows a highly nonlinear stress-strain response. The frictional behavior of human skin at the tissue scale (in the order of cm) is affected by several variables including age [25,26], anatomical region [27][28][29], contact material [30], type of contact [5,31], environmental conditions [6,26,28], and hydration of the tissue [16,32]. However, to discriminate between the relative contributions of these factors, it is advantageous to zoom in to the mesoscopic scale, in the order of hundreds of μm to a few mm.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental studies have shown that the interaction of the human skin with different materials and surfaces can show coefficient of friction over a wide range, between 0.059 and 3.7 [101,43,102]. Although our analysis does not represent the interaction between the human skin and particular materials, values of =0.25 have been reported for the interaction between calf skin and nitrocellulose [29], =0.22 for the contact between forearm skin and stainless steel [103], =0.22 between forearm and polypropylene and between different body zones and Teflon [27], and =0.19 between forearm skin and steel [43] among other similar values to the local coefficient of friction considered here. Previous work considering rigid indenters and soft substrate showed that the reaction forces on the indenter are not just due to the local friction but that an asymmetric deformation field on the length scale of the indenter can contribute a significant deformation component [33,34,85].…”
Section: The Primary Skin Lines In the Microrelief Influence The Globmentioning
confidence: 84%
“…It operates physiologically in the large deformation regime and shows a highly nonlinear stress-strain response. The frictional behavior of human skin at the tissue scale (in the order of cm) is affected by several variables including age [25,26], anatomical region [27,28,29], contact material [30], type of contact [5,31], environmental conditions [6,26,28], and wetness in the tissue [32,16]. However, to discriminate between the relative contributions of these factors, it is advantageous to zoom in to the mesoscopic scale, in the order of hundreds of m to a few mm.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] These natural prototypes inspired the development of artificial surfaces with unidirectional wetting properties allowing the transport of liquid droplets. [ 4,6,7 ] Another interesting case is the frictional anisotropy of snake scales [ 8–13 ] enabling snakes to locomote efficiently, even on slippery or inclined surfaces. While some snakes use the edges of their ventral scales to climb even trees, [ 10 ] many snakes feature oriented micron‐sized fibrils with nanoscale steps causing anisotropic friction along their body ( Figure a).…”
Section: Introductionmentioning
confidence: 99%